AN ANALYSIS OF GRADE XI STUDENTS’ PERCEPTION OF CAKE APPLICATION IN LEARNING SPEAKING AT SMA YAYASAN DAYAH DARUL - Dara, Muetya Permata; Erlita, Yeni (Universitas Negeri Medan, 2023)
The aim of this study was to investigate the students’ perception by Cake application in speaking skill. This study was conducted at XI grade of SMA Yayasan Dayah Darul Qur’an. The methodology of this study is qualitative descriptive research. The data was collected by distributing the questionnaire and interviews by divided the questionnaire into 3 aspects namely; cognitive, affective, conative. The findings show that Cake Application is appropriate for learning English, particularly for strengthening students’ speaking abilities. Based on questionnaire data of the cognitive, affective, and cognitive aspects which show that almost all students feel that Cake Application is easy to use and helps them in the learning process. The Cake Application is highly valuable since it teaches them more about learning English and how to improve their speaking talents. Students also enjoy using the application since it may change a repetitious method of learning into a speaking method of learning with the use of technology.